Dimensions of Informality in Bangladesh Labour Market and the Consequent Wage Penalty. Issue 2 (September 2019) - Rahman, Mustafizur; Bhattacharya, Debapriya; Al-Hasan, Md
The article examines the various dimensions and underlying causes of informal employment in the Bangladesh labour market and the associated wage penalty. Based on labour force survey data for successive points, we trace the dynamics of employment in Bangladesh along the informal–formal divide over time. Given that wage differential remains a key feature concerning the two market segments, we have carried out mean and quantile decomposition exercises to estimate the wage penalty originating from informality. We find significant wage gaps between formal- and informal-paid employees, formal paid and informal day labour, and formal paid and informal self-employed. The wage gaps range between 65.0 per cent and 225.0 per cent. The gap arises from a combination of observed differences in human capital and job characteristics, and the wage premium accruing from formal employment. JEL: C21, J31